Boplang as ‘Urf in Islamic Law: Exploring the Transformation of Ritual Practices into Building Regulations - Sarip Sarip; Gumiwang Tri Anugrah Tien Tono Putri; Sri Maryati; Axesa Haraja Saputra (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
The existence of customary law in the process of building a house's foundation, particularly the boplang tradition in Cirebon, is still very strong. Yet, modern society greatly desires simplicity and practicality, relying solely on positive law. Therefore, this article explores how Islamic law support and challenge boplang as a form of ‘urf in Cirebon, assess the societal and legal status within the local community and National law. Using an anthropological approach to law and framed within Islamic legal theory, especially the concept of ‘urf (custom), this study applies a qualitative method based on in-depth interviews with community leaders, cultural practitioners, and village officials. The study aims to identify and articulate the normative values embedded in boplang as a dynamic and living legal tradition. Findings indicate a persistent reliance on myth and oral tradition within the local community, which, although constitutionally protected, remains undocumented—thereby weakening its application of positive law from neighboring jurisdictions perceived as more authoritative. The study concludes that rationalizing boplang through systematic documentation and interpretation grounded in Islamic legal norms can strengthen its legitimacy law is often regarded as more flexible, adaptive, and context-sensitive compared to the rigid nature of formal positive law.